Implementasi Kurikulum Berbasis English For Specific Purposes Pada Mahasiswa Batam Tourism Polytechnic (BTP) - Syamsidah Lubis; Dinn Wahyudin; Rusman Rusman (Faculty of Education Universitas Negeri Malang, 2020)
Abstract: This study aims to determine how the implementation of the English for Specific Purposes (ESP) curriculum in Batam Tourism Polytechnic (BTP) students in the Chamber Division (RDM) Management Study Program and the Tourism Management Study Program (F&B). This study used a descriptive method with a sample of all populations. The data collection techniques in this study were questionnaires (questionnaire), documentation study, and observation. The results of data processing show that the implementation carried out in the Room Division (RDM) Management Study Program and Food Management (F&B) Tourism Study Program always carry out activities that have been made in the RPS and implemented in learning. Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana implementasi kurikulum berbasis English for Specific Purposes (ESP) pada mahasiswa Batam Tourism Polytecnic (BTP) di Prodi Manajemen Divisi Kamar (RDM) dan Prodi Pariwisata Manajemen Tata Hidang (F&B). Penelitian ini menggunakan metode desktiptif dengan sampel semua populasi. Adapun teknik pengumpulan data dalam penelitian ini adalah kuesioner (angket), studi dokumentasi, dan observasi. Hasil dari pengolahan data menunjukkan bahwa implementasi yang dilakukan di Prodi Pariwisata Manajemen Divisi Kamar (RDM), dan Prodi Pariwisata Manajemen Tata Hidangan (F&B) selalu melakukan kegiatan-kegiatan yang telah dibuat dalam RPS dan diimplemtasikan dalam pembelajaran.